(NgOGOLX I nIKOLAEWSKAQ rOSSIQ (B/s - (NgUS(B, (NmIHAIL sEMENOWI^s; (NmA[INSKIJ(B, (Ns(B.s ((NmOSKWA (B:s (NhUDOV(B. (NLIT(B.,s, 1957)
(NiMEN(B. (NUKAZ(B.: (NS(B. 359-368s
Keywords: (NgOGOLX(B, (NnIKOLAJ wASILXEWI^s -- 1809-1852; (NrUSSKAQ LITERATURAs